Ichnofabrics from muddy shallow-water bottom current deposits, Upper Jurassic-Lower Cretaceous Vaca Muerta Formation, Argentina - Paz, Maximiliano (2021)
Fil: Paz, Maximiliano.University of Saskatchewan, Department of Geological Sciences, 114 Science Place, S7N 5E2 Saskatoon, Canada